Exploring LGBT resilience and moving beyond a deficit-model: findings from a qualitative study in England. Issue 1 (2nd January 2023) - Peel, Elizabeth; Rivers, Ian; Tyler, Allan; Nodin, Nuno; Perez-Acevedo, Caroliz
ABSTRACT: The aim of this study is to critique and extend psychological approaches to resilience by examining retrospective accounts of LGBT people in England who had directly experienced or witnessed events that were salient as significantly negative or traumatic. Pre-screening telephone interviews identified ten individuals who matched inclusion criteria (mean age: 39 years; range 26–62 years) as part of a larger study. Interviews were semi-structured and informed by a literature review undertaken at the start of the study. We identified three themes of that extend the resilience literature for LGBTQ+ people: (1) identifying and foregrounding inherent personal traits – how non-contextual inborn qualities or attributes needed external effort to be recognised and operationalised; (2) describing asymmetric sources of social support and acceptance – the importance of positive environment is unequally available to LGBT people compared to heterosexuals, and uneven within the LGBT group; and (3) blurring distinctions between resilience and coping – experiential approaches to moving beyond distress. We suggest that narratives of resilience in the accounts of LGBT people can inform the development of resilience promotion models for minoritized individuals and support movement away from deficit-focused approaches to health policy.